2011
DOI: 10.4028/www.scientific.net/msf.690.274
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ni on the High-Temperature Strength of Al-Si Cast Alloys

Abstract: In order to investigate the effect of Ni on the high-temperature strength of Al-Si cast alloys, tensile properties of hypoeutectic and eutectic alloys were determined at 250 °C after long-term annealing at test temperature. LOM- and SEM-analysis revealed the existence of Al3Ni-phases in close contact to eutectic Si. It was shown that the strength can be increased by the addition of Ni, though just to a certain level, depending on the fraction of eutectic phase in the alloy. The alloys were considered as a coar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…The compositions of the samples are shown in Table 1. The near eutectic alloys (1)(2)(3)(4)(5)(6)(7)(8) can be divided into an Mg containing (1)(2)(3)(4) and an Mg free group (5)(6)(7)(8), whereas the hypoeutectic alloys are sectioned according to the particular combination of the respective main alloying elements: 9-24 (Cu/Ni) and 25-36 (Cu/Mg). Additionally, all alloys contain Fe and Mn in an amount comparable to recycling Al-Si foundry alloys.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compositions of the samples are shown in Table 1. The near eutectic alloys (1)(2)(3)(4)(5)(6)(7)(8) can be divided into an Mg containing (1)(2)(3)(4) and an Mg free group (5)(6)(7)(8), whereas the hypoeutectic alloys are sectioned according to the particular combination of the respective main alloying elements: 9-24 (Cu/Ni) and 25-36 (Cu/Mg). Additionally, all alloys contain Fe and Mn in an amount comparable to recycling Al-Si foundry alloys.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in the last couple of years, several investigations were carried out with the objective of improving the mechanical properties of hypoeutectic and near eutectic Al-Si foundry alloys at elevated temperatures. [1][2][3][4][5][6] Specific alloying elements like Ni, Cu and Mg were observed to improve the high temperature strength of Al-Si foundry alloys to certain limits by various strengthening mechanisms. [1][2][3][4][5][6] However, the positive effect of the four classical strengthening mechanisms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [9] reported the HT tensile strength (350 o C) can be elevated from 42.74 MPa to 61.63 MPa with the introduction of Ni to form Al 3 CuNi and Al 7 Cu 4 Ni in Al-13 wt% Si alloy. Similarly, Stadler et al [10,12] added 2.11 wt% Ni into Al-12 wt% Si alloy, which can improve the HT strength (250 o C) from 90 (0 wt% Ni) to 120 MPa (2.11 wt% Ni).…”
Section: Introductionmentioning
confidence: 95%
“…The accelerated need for weight reduction, however, leads to higher mechanical and thermal loading of these aluminium castings in future vehicles, requiring improved Al-Si foundry alloys. Therefore, in the last couple of years, several investigations were carried out with the objective of improving the mechanical properties of Al-Si foundry alloys at elevated temperatures [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%